2022
DOI: 10.1371/journal.pone.0272137
|View full text |Cite
|
Sign up to set email alerts
|

Low mean HbA1c does not increase all-cause and cardiovascular mortality in patients with diabetes: Effect-modifications by anemia and chronic kidney disease stages

Abstract: Background Previous studies reported that low levels of glycated hemoglobin A1c (HbA1c) were associated with increased mortality. We investigated rates and risks of all-cause and cardiovascular mortality in association with mean HbA1c levels with stratification of anemia and chronic kidney disease (CKD) stages, major causes of low HbA1c. Methods 47,145 patients with prescription of antidiabetic agents >6 months in the outpatient visits (2003–2018) were linked to Taiwan’s National Death Registry to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We observed that those patients with mean HbA1c <6.0% consisted of minor portions of all levels of hypoglycemia (~4%). HbA1c value might be underestimated in patients with diabetes in the status of advanced chronic kidney disease and anemia, and hypoglycemia was more frequent in those with mean HbA1c 7.0–9.9% rather than in those with mean HbA1c <6.0% in our previous study [ 12 ]. Similar to our findings, in the diabetes and aging study of Kaiser Permanente North California integrated healthcare delivery system, hypoglycemia was common in all levels of glycemic control, and the authors did not find patients with the lowest HbA1c levels were at high risk of hypoglycemia [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…We observed that those patients with mean HbA1c <6.0% consisted of minor portions of all levels of hypoglycemia (~4%). HbA1c value might be underestimated in patients with diabetes in the status of advanced chronic kidney disease and anemia, and hypoglycemia was more frequent in those with mean HbA1c 7.0–9.9% rather than in those with mean HbA1c <6.0% in our previous study [ 12 ]. Similar to our findings, in the diabetes and aging study of Kaiser Permanente North California integrated healthcare delivery system, hypoglycemia was common in all levels of glycemic control, and the authors did not find patients with the lowest HbA1c levels were at high risk of hypoglycemia [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
“…FEMH, a tertiary medical center, has set up its electronic medical database of out-patient and emergency visits since 2001 and 2008, respectively. The details of our out-patient electronic database have been described in previous studies [12][13][14]. In this study, we extended our database to emergency visits electronic records.…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The age of each study subject was determined using the difference between the index date and the date of birth. Similar to the study design of our previous reports ( Ooi et al., 2022 ; Yeh et al., 2022 ), we collected all information on oral antidiabetic agents, insulin, antihypertensive, and antilipid medications (statins and fibrates) between the index date and the end of follow-up, which is either death or censoring. Various cardiovascular risk factors (coronary artery disease (ICD-9-CM: 410, 411, 413, 414 or ICD-10-CM: I20-I25), heart failure (ICD-9-CM: 428 or ICD-10-CM: I50), and cerebrovascular disease (ICD-9-CM: 433-436, 437.0, 437.1 or ICD-10-CM: I63-I66, I67.2, I67.3, I67.6, I67.81, I67.82, I67.9)) retrieved from the outpatient medical records between the index date and the end of follow-up were considered as potential confounders ( Glasheen, Renda & Dong, 2017 ).…”
Section: Methodsmentioning
confidence: 99%